2018
DOI: 10.3389/fneur.2018.00490
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Biomarkers Are Associated With Glial Fibrillary Acidic Protein and αII-spectrin Breakdown Products in Brain Tissues Following Penetrating Ballistic-Like Brain Injury in Rats

Abstract: Treatments to improve outcomes following severe traumatic brain injury (TBI) are limited but may benefit from understanding subacute-chronic brain protein profiles and identifying biomarkers suitable for use in this time. Acute alterations in the well-known TBI biomarkers glial fibrillary acidic protein (GFAP), αII-spectrin, and their breakdown products (BDPs) have been well established, but little is known about the subacute-chronic post-injury profiles of these biomarkers. Thus, the current study was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Thus, APP positive cells likely contain a mixture of intact as well as cleaved peptides ( Burton et al, 2008 ; Wahrle et al, 2008 ; Muresan et al, 2009 ). The PBBI model does not replicate amyloidosis (plaques) per se , but it does lead to drastic fragmentation of many neuronal proteins ( DeDominicis et al, 2018 ), inclusive of APP as previously mentioned, in addition to tissue loss in a manner that is much more drastic than CCI or FPI ( Mountney et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, APP positive cells likely contain a mixture of intact as well as cleaved peptides ( Burton et al, 2008 ; Wahrle et al, 2008 ; Muresan et al, 2009 ). The PBBI model does not replicate amyloidosis (plaques) per se , but it does lead to drastic fragmentation of many neuronal proteins ( DeDominicis et al, 2018 ), inclusive of APP as previously mentioned, in addition to tissue loss in a manner that is much more drastic than CCI or FPI ( Mountney et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This model has been extensively characterized; several studies have found that key features are generally highest at 1, 3, or 7 days post-injury. For instance, blood brain barrier disruption is greatest within 1 day ( Cunningham et al, 2014 ), while indices of inflammation, cell loss, and protein fragmentation are prominent at 3–7 days post-injury ( Boutte et al, 2016 , 2020 ; Cartagena et al, 2016 ; DeDominicis et al, 2018 ). Collectively, these features are involved in severe TBI progression for which miRNA may be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin C-terminal hydrolase-L1 (UCH-L1) is a deubiquitinating enzyme enriched in neuronal cell bodies (17). GFAP and UCH-L1 are the most widely used biomarkers for acute, moderate-to-severe TBI (18)(19)(20)(21). Tau, an important microtubule-associated structural element of the neuronal cytoskeleton (22).…”
Section: Introductionmentioning
confidence: 99%
“…The same search filters were applied, leading to 295 results being excluded while a further 71 duplicates were removed using EndNote 20 [ 30 ]. A total of 140 papers were manually excluded following assessment against the selection criteria, leaving a total of 24 papers eligible for inclusion in the review [ 36 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Figure 2 provides an overview of the protein literature search and study selection process.…”
Section: Resultsmentioning
confidence: 99%